Telemonitoring-based service redesign for the management of uncontrolled hypertension (HITS): cost and cost-effectiveness analysis of a randomised controlled trial. Issue 5 (23rd May 2013) - Stoddart, Andrew; Hanley, Janet; Wild, Sarah; Pagliari, Claudia; Paterson, Mary; Lewis, Steff; Sheikh, Aziz; Krishan, Ashma; Padfield, Paul; McKinstry, Brian
Abstract : Objectives: To compare the costs and cost-effectiveness of managing patients with uncontrolled blood pressure (BP) using telemonitoring versus usual care from the perspective of the National Health Service (NHS). Design: Within trial post hoc economic evaluation of data from a pragmatic randomised controlled trial using an intention-to-treat approach. Setting: 20 socioeconomically diverse general practices in Lothian, Scotland. Participants: 401 primary care patients aged 29–95 with uncontrolled daytime ambulatory blood pressure (ABP) (≥135/85, but <210/135 mm Hg). Intervention: Participants were centrally randomised to 6 months of a telemonitoring service comprising of self-monitoring of BP transmitted to a secure website for review by the attending nurse/doctor and patient, with optional automated patient decision-support by text/email (n=200) or usual care (n-201). Randomisation was undertaken with minimisation for age, sex, family practice, use of three or more hypertension drugs and self-monitoring history. Main outcome measures: Mean difference in total NHS costs between trial arms and blinded assessment of mean cost per 1 mm Hg systolic BP point reduced. Results: Home telemonitoring of BP costs significantly more than usual care (mean difference per patient £115.32 (95% CI £83.49 to £146.63; p<0.001)). Increased costs were due to telemonitoring service costs, patient training and additional general practitioner and nurse consultations. The mean cost of systolic BP reduction was £25.56/mm Hg (95% CI £16.06 to £46.89) per patient. Conclusions: Over the 6-month trial period, supported telemonitoring was more effective at reducing BP than usual care but also more expensive. If clinical gains are maintained, these additional costs would be very likely to be compensated for by reductions in the cost of future cardiovascular events. Longer-term modelling of costs and outcomes is required to fully examine the cost-effectiveness implications. Trial registration: International Standard Randomised Controlled Trials, number ISRCTN72614272 .